Zabolotsky's Love Poems as a Part of the Poetic World - MKHITARYAN, KARINE (Bulletin of Yerevan University H: Russian Philology, 2021)
The love poems by Zabolotsky are characterized by images of the Universe, death and immortality. This gives poems on a love topic of deep philosophical significance. The love poems also content a new understanding of the concept of the mind, a characteristic feature of which is soulfulness.
Keywords: Zabolotsky,“The last love”, time, space, the Universe, death, immortality, soul